Unnecessary Roughness? School Sports, Peer Networks, and Male Adolescent Violence - Kreager, Derek A. (American Sociological Review, 2007)
This article examines the extent to which participation in high school interscholastic sports contributes to male violence. Deriving competing hypotheses from social control, social learning, and masculinity theories, I use data from the National Longitudinal Study of Adolescent Health to test if (1) type of sport and (2) peer athletic participation, contribute to the risks of male serious fighting. Contrary to social control expectations, analyses suggest that athletic involvement fails to inhibit male violence. Moreover, there is a strong relationship between contact sports and violence. Football players and wrestlers, as opposed to baseball, basketball, tennis, and other athletes, are significantly more likely than nonathletic males to be involved in a serious fight. Additionally, the direct effect of football is explained by the football participation of individuals' peers. Males whose friends play football are more likely to fight than other males, supporting perspectives that emphasize peer contexts as important mediators. Overall, findings are consistent with the expectations of social learning and masculinity arguments. The theoretical and policy implications of these results are discussed.